Numerical Simulations of Shear Driven Square and Triangular Cavity by Using Lattice Boltzmann Scheme - Abdul Munir, Fudhail; Sidik, N.A.C; Mohamad Zin, Mohd Rody; Hassan, Muhammad Zahir; Mohd Tahir, Musthafah (World Academy of Science, Engineering and Technology, 2010)
In this paper, fluid flow patterns of steady incompressible flow inside shear driven cavity are studied. The numerical simulations are conducted by using lattice Boltzmann method (LBM) for different Reynolds numbers. In order to simulate the flow, derivation of macroscopic hydrodynamics equations from the continuous Boltzmann equation need to be performed. Then,the numerical results of shear-driven flow inside square and triangular cavity are compared with results found in literature review. Present study found that flow patterns are affected by the geometry of the cavity and the Reynolds numbers used.